Focal Extravasated Mucin in Breast Core Needle Biopsies: Is Surgical Excision Always Necessary?. Issue 3 (28th March 2013) - Edelweiss, Marcia; Corben, Adriana D.; Liberman, Laura; Kaplan, Jennifer; Nehhozina, Tatjana; Catalano, Jeffrey P.; Brogi, Edi
Abstract Focal extravasated mucin (EM) with benign or atypical epithelium is a rare finding at breast core needle biopsy (CNB) and usually prompts surgical excision to rule out mucin‐producing carcinoma. In the largest detailed series to date, we assessed surgical outcomes in lesions yielding EM with atypical or nonatypical epithelium at CNB. With IRB approval, we retrospectively reviewed 28 consecutive atypical and nonatypical CNBs with EM that underwent surgical excision at our center over a 22‐year period. CNB imaging and pathologic findings were concordant if pathology sufficiently explained the radiologic features of the lesions. Pathologic findings in CNB and excision specimens were correlated. Statistical analysis was performed. CNBs sampled mammographic calcifications in 25/28 (89%) women and a mass in 3/28 (11%). All cases had concordant pathologic and imaging findings. At CNB, the epithelium associated with EM was atypical in 18/28 (64%) lesions and nonatypical in 10 (36%). Cancer (one mucinous carcinoma; three ductal carcinoma in situ) was present in 4/28 excision specimens (14%; 95% confidence intervals [CI], 4%–33%). All carcinomas were in lesions with epithelial atypia at CNB (4/18; 22%; 95% CI, 6%–48%) versus none (0/10; 0%; 95% CI, 0%–31%) in nonatypical lesions at CNB; this difference was not statistically significant (p = 0.3). Surgery is warranted for lesions yielding EM with atypia at CNB due to the high (22%) prevalence of cancer. Our data suggest that surgical excision of lesions yielding EM without epithelial atypia at CNB may not be necessary provided that imaging and pathologic findings are concordant.